2021
DOI: 10.3389/fphys.2021.557514
|View full text |Cite
|
Sign up to set email alerts
|

Volume Load-Induced Right Ventricular Failure in Rats Is Not Associated With Myocardial Fibrosis

Abstract: BackgroundRight ventricular (RV) function and failure are key determinants of morbidity and mortality in various cardiovascular diseases. Myocardial fibrosis is regarded as a contributing factor to heart failure, but its importance in RV failure has been challenged. This study aims to assess whether myocardial fibrosis drives the transition from compensated to decompensated volume load-induced RV dysfunction.MethodsWistar rats were subjected to aorto-caval shunt (ACS, n = 23) or sham (control, n = 15) surgery,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…We also analyzed a potential association between SLIT3 expression and cardiac fibrosis in myocardial samples obtained from normal controls, patients with tetralogy of Fallot, where cardiac fibrosis is anticipated from the pressure overload, 32 and those with ventricular septal defect, where less cardiac fibrosis is anticipated from this volume overload defect. 33 We found that SLIT3 transcript levels were significantly correlated with COL1A1 transcript levels when considering all patient and control samples ( Figure S1B ). Furthermore, higher SLIT3 and COL1A1 transcript levels were found in myocardial samples taken from pressure overload defect patients ( Figure S1B ).…”
Section: Resultsmentioning
confidence: 82%
“…We also analyzed a potential association between SLIT3 expression and cardiac fibrosis in myocardial samples obtained from normal controls, patients with tetralogy of Fallot, where cardiac fibrosis is anticipated from the pressure overload, 32 and those with ventricular septal defect, where less cardiac fibrosis is anticipated from this volume overload defect. 33 We found that SLIT3 transcript levels were significantly correlated with COL1A1 transcript levels when considering all patient and control samples ( Figure S1B ). Furthermore, higher SLIT3 and COL1A1 transcript levels were found in myocardial samples taken from pressure overload defect patients ( Figure S1B ).…”
Section: Resultsmentioning
confidence: 82%
“…These studies demonstrated that conventional parameters are susceptible to changes in loading conditions. Hagdorn et al reported that TAPSE remained unchanged in their chronic over-preloading rat model study, while Ees gradually decreased, revealing that TAPSE might miss RV dysfunction in chronic volume overloading conditions ( 8 ). Furthermore, we previously reported that TAPSE was not a significant predictor of mortality in a PH cohort because TAPSE can be pseudo-normalized by a lowered RV afterload in severe tricuspid regurgitation (TR) ( 17 ).…”
Section: Manuscriptmentioning
confidence: 99%
“…Conventional parameters such as tricuspid annular plane systolic excursion (TAPSE), systolic tissue Doppler velocity of the tricuspid annulus (RV S’), and RV fractional area change (FAC) have been currently used for RV function evaluation; however, these conventional parameters have several limitations, one of which is the load-dependency. Their values change depending on the hemodynamic load exerted on the RV, leading to inaccurate assessment of RV function ( 6 8 ). Since a diseased RV is consistently under complex loading conditions, load dependency is a significant issue that must be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial fibrosis is a manifestation of an adaptive response by the heart to pressure overload. Accordingly, fibroblasts undergo differentiation into myofibroblasts to counter this imposed stress that suppresses cardiac function (Hagdorn et al, 2021). This shift is reflective of a healthy myocardium response in which some of the fibroblast markers that include α‐smooth muscle actin (α‐SMA), collagen I, and collagen III, are not expressed (Czubryt & Hale, 2021; Gritsenko et al, 2020).…”
Section: Introductionmentioning
confidence: 99%